Aspergilloma in post COVID-19 patient - Arjun Kumar; Avishek Layek; Rahul Kumar Gupta; Manju Bala; Akhlesh (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2021)
A 61-year-old male admitted with complaints of increased shortness of breath, right chest pain and blood-tinged sputum expectations for the past 5 days. He was recently treated for COVID-19 infection at home with 6 days of oral corticosteroid and other symptomatic medication. He denied any other significant past medical history. He was recently diagnosed with type 2 diabetes mellitus. He is a chronic smoker and occasionally takes alcohol for the past 25 years. On chest auscultation the right-side air entry was diminished and rest of systemic examination was normal. Routine blood investigation was normal except raised fasting blood sugar levels.